Best resumes for scientists and engineers - Lewis, Adele 1924-1990 (Wiley, 1993)
One lesson of the tough employment market of the 1990s is that every job-seeker needs a resume customized to highlight his or her particular strengths in powerful and effective terms. This is particularly important for scientists and engineers, who until now have enjoyed a "buyer's" market.